Caballero a la medida - Cantinflas, 1911-1993; Delgado, Miguel M., 1905-1994; Garasa Berges, Ángel, 1905-1976; Ruvinskis, Wolf; Salvador, Jaime; Soler, Domingo; Valdez, Martha (Playa Films, 2006)
Comedia de confusión de identidad, asesinato, boxeo y un monasterio.